Spontaneous pneumothorax as a complication in COVID‐19 recovered male patient: a case report from a tertiary care centre in Central India - Wajid, Sheikh; Kela, Manoj; Bawa, Abhishek; Harchandani, Rohit; Vora, Ashish; Bhandari, Vinod; Sharma, Rajesh; Doshi, Ravi (International Journal of Research in Medical Sciences, 2021)
As the number of COVID-19 cases emerge new complications associated with the disease are recognised. This report records a case of pneumothorax in a COVID-19 patient. Our report justifies that pneumothorax can occur during different phases of disease in patients without any history of pulmonary comorbidity and is not necessarily associated to positive pressure ventilation or a severity of COVID-19. However debatable might be the exact mechanism of the process be, this observation might imply that extensive alveolar destruction due to COVID-19 may lead to bulla formation resulting in subsequent pneumothorax.